Nb2O5 Used as Photocatalyst for Degradation of Eosin-Y Using Solar Energy - GANDHI, JAYANT; VERMA, NIKHIL; BHARDWAJ*, SHIPRA (Asian Journal of Chemistry, 2009)
The photocatalytic degradation of eosin-Y was studied using Nb2O5 as semiconductor. Visible light is used as the source of energy. The effect of various parameters like amount of semiconductor, pH, light intensity, dye concentration, etc. on the photodegradation are investigated. Atentative mechanism is proposed.